In the Supreme Court of the United States, October term, 1985, Cargill, Inc. and Excel Corporation, petitioners v. Monfort of Colorado, Inc. : on petition for a writ of certiorari to the United States Court of Appeals for the Tenth Circuit : brief for the United States as amicus curiae. (1985)
Summary goes here